Estrategia pedagógica para la formación de ingenieros con discapacidad visual - Fernández Morales, Flavio Humberto (2015)
Fil: Fil: Fernández Morales, Flavio Humberto. Universidad Pedagógica y Tecnológica de Colombia; Colombia